2014
DOI: 10.4490/algae.2014.29.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sustainable land-based Gracilaria cultivation system

Abstract: Land-based seaweed (Gracilaria) cultivation systems may provide products with high quality and biosafety for human consumption, as well as for other high value applications. However, a limitation for this land based system is high management costs. The objective of this study was to determine if the management costs for Gracilaria cultivation can be reduced without a decrease in productivity by using CO 2 injection along with a high stocking density and high photosynthetically active radiation (PAR), and comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…We predict that mass production of this species in China will increase in response to OA and eutrophication. Kim and Yarish (2014) indicated that productivity of Gracilaria sp. was enhanced under elevated CO 2 levels with high stocking density and irradiance.…”
Section: Discussionmentioning
confidence: 99%
“…We predict that mass production of this species in China will increase in response to OA and eutrophication. Kim and Yarish (2014) indicated that productivity of Gracilaria sp. was enhanced under elevated CO 2 levels with high stocking density and irradiance.…”
Section: Discussionmentioning
confidence: 99%
“…Control of pH and CO 2 is readily achieved with on‐land cultures and pH stress may be an effective tool for influencing real‐time bioactivity content (Kim and Yarish ). Other chemical stresses have been implicated in bioactive content variability and some of these can ethically and cost effectively be applied during on‐land cultivation (e.g., oxidants).…”
Section: Future Seaweed Cultivation For High Value Productsmentioning
confidence: 99%
“…In addition, and when practiced in simple plastic film-covered greenhouses, the method allows for day-time introduction of CO 2 -rich flue gases from industrial point sources directly into head-spaces of the plastic-covered greenhouses, providing inexpensive, recycled inorganic carbon to the drip irrigated seaweeds. Moreover, one important advantage also of land-based cultivation, including the drip irrigation methods, is the ease and flexibility of controlling the culture system [ 28 , 29 ]. This ensures that production meets high quality standards and biosafety for human and animal consumption, as well as for other high value applications such as cosmeceutical or pharmaceutical products.…”
Section: Introductionmentioning
confidence: 99%